Effects of Unloading Groundwater on Aquifer Sorage and Water Availability - Moiwo , Juana P.; K. Kawa , Yahaya; M. H. Conteh, Alhaji; P. Kaisam, John (Current Advances in Geography, Environment and Earth Science Vol. 1, 2021)
It is long known that excessive groundwater withdrawal can cause land subsidence [1]. There is progressively excessive water resources exploitation in northern China, spurred by decades of aggressive food self-sufficiency drive [2]. In this agro-politically sensitive region, large areas of groundwater depletion cone and land subsidence are associated with an unprecedented water resources mining [3]. However, studies on water storage depletion and/or land subsidence in the region are largely statistical and fragmented in nature [3,4]. Here in this study, crustal unloading-controlled land deformation is estimated from anomaly trends in GRACE (Gravity Recovery and Climate Experiment) and InSAR (Interferometric Synthetic Aperture Radar) satellite observations, GLDAS (Global Land Data Assimilation System) model products and measured groundwater depth data. Estimated land subsidence for the 2002-2009 study period is 17.7\(±\)4.7 cm, which, given the average specific yield of 0.13, is the equivalent of 13.6±0.3 mm in groundwater storage loss or 104.6 mm of aquifer depletion. For the 843 000 km2 study area, annual storage depletion is estimated at 63.8±9.3 mm (53.8±7.8 km3) for total water storage, 58.3±5.3 mm (49.6±4.5 km3) for groundwater storage and 3.4±0.6 mm (2.8±0.5 km3) for soil water storage. The estimated total water storage depletion exceeds the projected 45 km3 annual water delivery by the South-North Water Diversion Project in 2050. Water storage depletion in combination with especially land subsidence in the region can have adverse implications for agricultural, industrial, socio-economic and political stability in the country. It is critical for the farmers and other stakeholders to embark on meaningful water-saving measures. Such measures should also be backed up with the tapping of alternative water sources (as the South-North Water Diversion Project) to supplement local water resources. Measures of this nature not only prevent further pumping-related issues and disruptions in food production, supply and security, but also ensure stable socio-economic growth.